2021
DOI: 10.1007/s11663-021-02310-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Grain Refiner, Inclusion Level, and Filter Grade on the Filtration Performance of Aluminum Melt

Abstract: The addition of grain refiner particles in the aluminum melt is known to reduce the filtration efficiency of ceramic foam filter (CFF). In the present work, a systematic study on the influence of the addition level of Al-Ti-B master alloys and the inclusion level on the filtration performance of aluminum melt has been investigated by pilot-scale filtration tests using 50 PPi and 80 PPi filters. The inclusion level of the melt has been measured using both LiMCA and PoDFA. For 80 PPi CFF, the N20 inclusion (diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In both our own research (Figure 10) and that of others [6,27], borides have been found to inhibit the flow of liquid metal through the Prefil Footprinter ® filter. According to the authors of Yang et al [28], the reduction in efficiency is due to the strong adherence of TiB 2 particles to oxide films in the filter. The adherence and agglomeration of heavy grain refiner particles onto oxide films counter the gravitation number of oxide films, making them difficult to be filtrated [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both our own research (Figure 10) and that of others [6,27], borides have been found to inhibit the flow of liquid metal through the Prefil Footprinter ® filter. According to the authors of Yang et al [28], the reduction in efficiency is due to the strong adherence of TiB 2 particles to oxide films in the filter. The adherence and agglomeration of heavy grain refiner particles onto oxide films counter the gravitation number of oxide films, making them difficult to be filtrated [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors of Yang et al [28], the reduction in efficiency is due to the strong adherence of TiB 2 particles to oxide films in the filter. The adherence and agglomeration of heavy grain refiner particles onto oxide films counter the gravitation number of oxide films, making them difficult to be filtrated [28]. This can also lead to the inhibition of the filtration process during alloy casting.…”
Section: Discussionmentioning
confidence: 99%
“…In both our own research (Figure 10) and that of others [23,24], borides have been found to inhibit the flow of liquid metal through the Prefil Footprinter ® filter. According to the authors of Yang et al [25] the reduction of efficiency is due to the strong adherence of TiB2 particles to oxide films in the filter. The adherence and agglomeration of heavy grain refiner particles onto light oxide films counter the gravitation number of oxide films, making them difficult to be filtrated [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors of Yang et al [25] the reduction of efficiency is due to the strong adherence of TiB2 particles to oxide films in the filter. The adherence and agglomeration of heavy grain refiner particles onto light oxide films counter the gravitation number of oxide films, making them difficult to be filtrated [25]. This can also lead to inhibition of the filtration process during alloy casting.…”
Section: Discussionmentioning
confidence: 99%